Genetic Variants Are Not Associated with Outcome in Patients with Coronary Artery Disease and Left Ventricular Dysfunction: Results of the Genetic Sub-study of the Surgical Treatment for Ischemic Heart Failure (STICH) Trials - Feldman, Arthur M. (Cardiology, 2015)
OBJECTIVES AND BACKGROUND: We evaluated the ability of 23 genetic variants to provide prognostic information in patients enrolled in the Genotype Sub-studies of the Surgical Treatment for Ischemic Heart Failure (STICH) trials. METHODS: Patients in STICH Hypothesis 1 were randomized to medical therapy with or without CABG (Coronary Artery Bypass Grafting). Those in STICH Hypothesis 2 were randomized to CABG or CABG with left ventricular reconstruction. RESULTS: In patients assigned to STICH Hypothesis 2 (n=714), no genetic variant met the pre-specified Bonferroni-adjusted threshold for statistical significance (p<0.002); however, several met nominal prognostic significance: variants in the β2-adrenergic receptor gene (β(2)-AR Gln27Glu) and in the A1-adenosine receptor gene (A1-717 T/G) were associated with an increased risk of a subject dying or being hospitalized for a cardiac problem (p=0.027 and 0.031, respectively). These relationships remained nominally significant even after multivariable adjustment for prognostic clinical variables. However, none of the 23 genetic variants influenced all-cause mortality or the combination of death or cardiovascular hospitalization in the STICH Hypothesis 1 population (n=532) by either univariate or multivariable analysis. CONCLUSION: We were unable to identify the predictive genotypes in optimally treated patients in these two ischemic heart failure populations.